If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -10(12x + -5) = -5(x + 11) Reorder the terms: 10x + -10(-5 + 12x) = -5(x + 11) 10x + (-5 * -10 + 12x * -10) = -5(x + 11) 10x + (50 + -120x) = -5(x + 11) Reorder the terms: 50 + 10x + -120x = -5(x + 11) Combine like terms: 10x + -120x = -110x 50 + -110x = -5(x + 11) Reorder the terms: 50 + -110x = -5(11 + x) 50 + -110x = (11 * -5 + x * -5) 50 + -110x = (-55 + -5x) Solving 50 + -110x = -55 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 50 + -110x + 5x = -55 + -5x + 5x Combine like terms: -110x + 5x = -105x 50 + -105x = -55 + -5x + 5x Combine like terms: -5x + 5x = 0 50 + -105x = -55 + 0 50 + -105x = -55 Add '-50' to each side of the equation. 50 + -50 + -105x = -55 + -50 Combine like terms: 50 + -50 = 0 0 + -105x = -55 + -50 -105x = -55 + -50 Combine like terms: -55 + -50 = -105 -105x = -105 Divide each side by '-105'. x = 1 Simplifying x = 1
| 3b-5-6b-8= | | D-7-(-25)= | | 4x+24=5x-2 | | 28/-4=3m-7m | | (.5)+(-.3333)+(.25)= | | 4x+24+5x-2=180 | | 4x-6y-2=0 | | 6w-w+4w= | | 2b-6+3b=-9 | | 7x+9y=-23 | | x=(y-9/3) | | (12x+1)+2(x-4)-(x-1)= | | -6|-2+b|=-42 | | -v(v+7)-3(1-6v)=0 | | 3(6r-1)-7(1-3r)=68 | | x+3x+17=133 | | 7x+10+3x-30=180 | | (4/3)w=75 | | -6-3-(-2)= | | 7/4p-2=5 | | 2y+3=-7+5y | | 2-1(1/15) | | -1=5/6 | | 8x-4+2x+4=180 | | 12+8*3+7= | | (3x-7)+(x+5)=180 | | -7(1-3b)+b(8b-6)=0 | | 3p+8p= | | -m/10+2=-4 | | 8-(-4)-(-5)= | | 2x+11+8x-1=180 | | 3n-4n=4 |